Particle Becomes Energy = Energy Becomes Mass (Global Journal of Science Frontier Research, 2023)
Each and every living thing on planet earth consists of at least one or more cells in their structure as an organism. A cell within each living thing has a chemical makeup that produces energy and is found in molecules that are supplied through its nutrition from the organism. This is considered the cell's food source. Energy is produced as the cell breaks down its nutritional source from the organism then, the cell can perform functions that it generally carries out. From the energy produced the cell has the ability to provide respiration, create hormones, enzymes, and perform other functions that the cell carries out. In energy transference a particle moves into a cell, as the cell increases in mass it increases in density as density increases and particles accumulate in the cell, the cell is forced to expand. As the cell expands energy is created from the particles and energy is released. When energy is created and released the cell divides into two cells then the process replicates itself as long as there are particles that are moving into the cell to create energy. After the cell divides, particles have lost their energy until new particles move into the cell and begin the process again. For a particle to move into the cell a vacuum may be created to pull the particle to the cell.
Keywords: life is quantum biology; tiȇu equation; particle becomes energy; energy becomes mass